2008
DOI: 10.1097/gco.0b013e32830866f4
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for medical care of children evaluated for suspected sexual abuse: an update for 2008

Abstract: The recommendations for the timing and type of examinations for prepubertal children, in contrast to adolescent sexual assault victims, may need to be changed. Studies showing that partial tears of the hymen, as well as abrasions and contusions, may heal to leave very little or no sign of previous injury emphasize the importance of urgent evaluations. There is a need for standardization of the training of medical professionals who perform child sexual abuse evaluations to ensure continuing competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 40 publications
1
41
0
9
Order By: Relevance
“…It is important to recognize these findings and to distinguish them from lesions caused by child abuse. 51 The Supplemental Appendix reviews genital and anal conditions that can be confused with sexual abuse.…”
Section: The Physical Examination When Sexual Abuse Is Suspectedmentioning
confidence: 99%
“…It is important to recognize these findings and to distinguish them from lesions caused by child abuse. 51 The Supplemental Appendix reviews genital and anal conditions that can be confused with sexual abuse.…”
Section: The Physical Examination When Sexual Abuse Is Suspectedmentioning
confidence: 99%
“…4 Guidelines suggest that anogenital warts in a child, in the absence of other indicators of abuse, is of indeterminate specificity for sexual transmission. 5 A retrospective review of children with anogenital warts referred to a sexual abuse clinic found that 31% were "likely sexually abused," but the likelihood of abuse increased with age. Children with anogenital warts who were four to eight years of age and over eight years were, respectively, 2.9 and 12.1 times more likely to have been abused than children less than four years of age.…”
Section: 2mentioning
confidence: 99%
“…Eckert et al (14) found in their study that the level of experience of the physicians who perform the examination caused significant differences in terms of determining and interpreting the findings after a sexual assault and the gender of the physician did not cause any difference. Therefore, the medical team who will evaluate the children who have been assaulted sexually should be educated periodically to have a standart level of knowledge (15).…”
Section: Sexual Child Abusementioning
confidence: 99%
“…In this case, determination of gonorrhea, chlamydia, syphilis and HIV etc. is a possible proof of sexual intercourse (4,15).…”
Section: Taking a Samplementioning
confidence: 99%